Does Infertility Affect the Sexual Function and Sexual Quality of Life of Women? A Case Control Study - POTUR, DİLEK; DEMİRCİ, NURDAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
Objectives: The study aimed to determine the effect of infertility on women's sexual function and sexual quality of life. Methods: In this case-control study, 316 infertile and 316 fertile women were interviewed in a hospital using the Index of Female Sexual Function and the Sexual Quality of Life Questionnaire-Female. Results: Sexual function scores of infertile women were lower than fertile women; however, the groups were similar in terms of sexual quality of life. Conclusion: The findings suggest a difference between fertile and infertile women in terms of sexual function, while the sexual quality of life was similar in both groups.
Keywords: Infertility; sexual function; sexual quality of life; MARITAL ADJUSTMENT; PREVALENCE; DYSFUNCTION; DEPRESSION; PREDICTORS; FERTIQOL; STRESS; IMPACT